2002
DOI: 10.1002/ijc.10406
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐induced leukemia risk among those aged 0–20 at the time of the Chernobyl accident: A case‐control study in the Ukraine

Abstract: A case-control study was conducted to estimate the radiation-induced acute leukemia risk for the period 1987-1997 among residents aged 0 -20 at the time of the Chernobyl accident in the most radioactively contaminated territories of the Ukraine (Rivno and Zhytomir regions). Data were collected on 272 leukemia cases diagnosed between 1 January 1987 and 31 December 1997. Of these, 98 cases were verified and interviewed. Verified cases were compared to 151 randomly selected controls matched by age, gender and typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…Particularly, Down syndrome for whom there is a reported 20-fold increased risk. Some studies have shown a risk with exposure to high level residential extremely low frequency electromagnetic fields [8][9][10].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Particularly, Down syndrome for whom there is a reported 20-fold increased risk. Some studies have shown a risk with exposure to high level residential extremely low frequency electromagnetic fields [8][9][10].…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, a recent study from the Ukraine is the first one indicating an increased risk for acute leukemia in the general population related to the Chernobyl accident [Noshchenko et al, 2002]. Recent studies outside the former USSR have also shown an increase in the thyroid cancer incidence suggested to be related to the accident [Cotterill et al, 2001;Gomez Segovia et al, 2004;Murbeth et al, 2004;Niedziela et al, 2004], but such studies have also failed to link an increase to the Chernobyl accident [Pillon et al, 1999;Szybinski et al, 2003].…”
Section: Introductionmentioning
confidence: 96%
“…Studies conducted in the most contaminated regions found an association between radiation exposure and leukemia risk in Ukraine, Belarus, but not in Russia, and they are not statistically significant [15][16][17]. A study conducted in Greece reported an increase in infant leukemia among infants who were in utero at the time of Chernobyl accident but those findings were based on a small cohort of 12 patients exposed and 31 unexposed [18].…”
Section: Discussionmentioning
confidence: 95%